Ecotourism Practices in Potatso National Park from the Perspective of Tourists: Assessment and Developing Contradictions - Rumin Zheng (MDPI AG, 2021)
Ecotourism in Potatso National Park has been developing for more than 15 years, which has had important guiding significance for the development of China’s national parks. This paper analyzes ecotourism practices in Potatso by extracting related travel notes and adopting the ground theory and content analysis method. The results show that the current ecotourism practices in Potatso include 5 dimensions and 15 elements. The five dimensions are the natural environment, environmental education, community participation, ecotourism experience and socioeconomic background. The five most important elements are the ecosystem elements, sensory and behavioral ecotourism experience, ecological facilities and interpretation systems. There are also three contradictions: between tourists’ environmental awareness and lack of environmental behaviors, between community participation and residents’ reception capacity, and between environmental education and tourists’ experiences. Regarding the future development of Potatso, conservation will always come first. A breakthrough is needed to strengthen the conversion of environmental education to the environmental behavior of tourists, adjust the participation model of communities dynamically, and continue innovating in the form of environmental education.